Legislasi Peraturan Daerah Partisipatif - La Ode Muhammad Iman Abdi Anantomo Uke (Al-'Adl, 2016)
Local Regulation legislation is the constitutional mandate of Article 18 (6), which reads "Local Government reserves the right to stipulate Regional Regulations and other regulations to implement autonomy and duty of assistance". In the implementation of legislation as a form of regional autonomy based on Law Number 23 Year 2014 on Regional Government, the public is entitled to provide input, either orally or in writing to the legislature as part of community participation in the area. The purpose of parsitipasi and community participation is to produce insights and perceptions that are useful from the communities involved (public interest) in order to improve the quality of decision-making, because people who are potentially affected as a result of the policy interest groups (interest groups), so that decision makers can capture the views, needs, and expectations of the community and the group, and then pour it into a concept that will be formed into regional regulation. Although public participation is less than ideal and not a guarantee that a law which generates will be effective in the community, but at least a step participatory adopted by the legislature in each establishment of laws, is expected to encourage the public to accept the presence of a Constitution.